Clinical Application of a Customized Gene Panel for Identifying Autism Spectrum Disorder-Associated Variants - Vittoria Greco; Donatella Greco; Simone Treccarichi; Maria Bottitta; Pinella Failla; Antonino Musumeci; Carla Papa; Valeria Chiavetta; Francesco Calì; Mirella Vinci (Medicina, 2025)
Background and Objectives: Autism spectrum disorder (ASD) is a neurodevelopmental disorder that belong to genetic and epigenetic mechanism. Despite the recent advantages in next-generation sequencing (NGS) technology, ASD etiology is still unclear. Materials and Methods: In this study, we tested a customized target genetic panel consisting of 74 genes in a cohort of 53 ASD individuals. The tested panel was designed from the SFARI database. Results: Among 53 patients analyzed using a targeted genetic panel, 102 rare variants were identified, with nine individuals carrying likely pathogenic or pathogenic variants considered genetically “positive.” We identified six de novo variants across five genes (POGZ 2 variants, NCOR1, CHD2, ADNP, and GRIN2B), including two variants of uncertain significance in POGZ p.Thr451Met and NCOR1 p.Glu1137Lys, one likely pathogenic variant in GRIN2B p.Leu714Gln, and three pathogenic variants in POGZ p.Leu775Valfs32, CHD2 p.Thr1108Metfs8, and ADNP p.Pro5Argfs*2. Conclusions: This study presents a comprehensive characterization of the targeted gene panel used for genetic analysis, while critically evaluating its diagnostic limitations within the context of contemporary genomic approaches. A pivotal accomplishment of this study was the ClinVar submission of novel de novo variants which expands the documented mutational spectrum of ASD-associated genes and enhances future diagnostic interpretation.